Communication, complexity and empire: The systemic thought of Harold Adams Innis. - Bonnett, John. (University of Ottawa (Canada), 2002)
Harold Innis is arguably the most influential social scientist Canada has ever produced. Nearly fifty years after his death in 1952, his writings on Canadian economic history and history of communication technologies are still highly regarded, still widely cited and still viewed as providing an exceptionally powerful framework for interpreting the histories of societies past and present. The problem, however, is that scholars remain uncertain as to the identity of Innis' framework due to his opaque writing style. There is also a sense in the literature that Innis' work on staples is conceptually linked with later studies tracing the impact of communication technology on the rise and fall of empires in the Near East and Europe. But without a clear conception of his framework, the relationship is difficult to assess. Some scholars have questioned whether Innis' work even has an underlying coherence. The purpose of this study is to suggest Innis' work should be construed as a sustained exploration of the nature of economic and social change. His purpose was to resuscitate the dynamic worldview he associated primarily with the writings of Adam Smith and biological disciplines such as ecology and embryology. To interpret Innis, this study uses the most contemporary expression of ecological change, namely that provided by the science of complexity. Through a reading of Innis' writings on staples, Political Economy in the Modern State, and his two major communication studies, this study suggests Innis' description of change contained several persistent features. The first is he studied systems comprised of multiple agents who by virtue of their interaction displayed emergent properties that persist over time. The North Atlantic trading network was one example. Innis also emphasised that his systems were governed by a variable that maintained a proper balance between freedom and constraint. Without it, self-organisation could not occur. In his early work, the variable was transportation. In the later studies, it was the quantity of circulating information. Finally, Innis pointed to systems governed by formal and final cause. They interacted with their surrounding environment to preserve their formal integrity, and regulate the activities of their constituent parts.
Keywords: History, Canadian.